Digest: Differentiating Fisherian sexual selection dynamics between haploids and diploids. (27th May 2020) - Peede, David
Abstract: Female mate preference for males displaying costly traits is a puzzling phenomenon found in nature. Fisher was the first to propose a formal model describing this paradoxical system of sexual selection. Despite the many models constructed from his theory, much remains unknown about its mechanics, especially in different genetic settings. Through simulations, Veller et al. compared population dynamics between haploids and diploids and found that Fisherian sexual selection acts differently on diploids compared to haploids due to linkage mechanisms.